Rapid antigen detection test (RADT) for pharyngitis diagnosis in children: Public and pharmacist perception - Aisha F. Badr; Raneyah A. Humedi; Nada A. Alfarsi; Haifa A. Alghamdi (Elsevier, 2021)
Background: Most common sought antibiotic-self treated infection globally is pharyngitis (sore throat). The aim of this study is to assess public's acceptance and potential use of Rapid Antigen Detection Test at community pharmacies in the diagnosis of bacterial pharyngitis in children prior to antibiotic dispensing in Saudi Arabia. Method: A qualitative cross-sectional study was conducted on October 2017. Two self-conducted questionnaires were used. One targeted the public above 21 years old and was distributed via social media. The other randomly targeted community pharmacists in Jeddah. Result: A total of 689 of the public and 40 community pharmacists completed the survey. Moreover, 571 (82.9%) of the public received antibiotics without a prescription; for symptoms related to sore throat (71%) followed by flu-like symptoms (24%). Only (3.77%) and (5%) of both public and community pharmacies have heard about RADT respectively, however the majority (93.03%) and (90%) of both respectively support its use in community pharmacies. Coded reasons for its use was mainly to decrease antibiotic misuse and/or abuse, increased specificity, decreased antibiotic side effects including bacterial resistance, and ease of use. Conclusion: Both public and community pharmacists support the idea of using RADT. Future efforts should look into pharmacist's role in providing point of care tests that are cost-effective and convenient for the public.